Variation of lexan polycarbonate properties by electron beam. Issue 3 (10th May 2012) - Hareesh, K.; Ranganathaiah, C.; Ramya, P.; Bhargavi, R.; Nair, Geetha G.; Sangappa,; Sanjeev, Ganesh
Abstract The modifications in microstructural, optical, and photoluminescence properties of the Lexan polycarbonate (bisphenol‐A‐polycarbonate) films exposed to different electron doses have been studied using UV–vis spectroscopy, Fourier transform infrared spectroscopy (FTIR), positron annihilation lifetime spectroscopy, photoluminescence spectroscopy, and scanning electron microscopy (SEM). The obtained UV–vis spectroscopy results showed decrease in optical energy gap, optical activation energy, and increase in number of carbon atoms per cluster with increase in electron dose. The chemical changes in electron irradiated polymers due to chain scission and reconstruction have been observed from FTIR spectroscopy. The correlation of positron lifetime study with optical measurement is obtained, and electron irradiation‐induced microstructural modifications within the polymer is understood. SEM result shows the degradation of Lexan polymer after electron irradiation. The mechanical properties and average molecular weight of Lexan decrease after irradiation, whereas average number of chain scissions per original polymer molecule increases. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013